Sprout production in pitahaya (Hylocereus sp.) grown in Guanacaste, Costa Rica: relation with climatic variables - Monge Pérez, José Eladio (2022)
The objective was to evaluate the relationship between sprout production in pitahaya (Hylocereus sp.) and climatic variables.  The trial was conducted in Santa Cruz, Guanacaste, Costa Rica, from January 2017 to November 2019.  Tested variables were: number of vegetative sprouts (NVS), number of reproductive sprouts (NRS), rainfall (R, in mm), relative humidity (RH, in %), average temperature (Ta, in ° C), maximum temperature (Tmax, in ° C), minimum temperature (Tmin, in °C), wind speed (WS, in m/s), and global radiation (GR, in MJ/m2).  Spearman correlations were calculated among all variables, except NRS.  NVS did not show significant correlations with any of the other variables; nevertheless, significant correlations of NVS were obtained with the climatic variables that occurred in the months prior to sprouting.  The production of vegetative sprouts did not present a defined pattern throughout the evaluated period, while the production of reproductive sprouts occurred only in 2019, in the early stage of the rainy season.  At the time of production of reproductive sprouts, the plants did not show production of vegetative sprouts.